Perlindungan Hukum Korban Tindak Pidana Kekerasan Fisik Dalam Perspektif Victimology - Noviyanti, Fitri; Putri, Sovi Ayudia (Universitas Sultan Ageng Tirtayasa, 2024)
A This study discusses legal protection for victims of physical violence from the perspective of victimology. This study aims to analyze the effectiveness of existing legal protections for victims of physical violence, as well as provide recommendations for improving the protection of victims of such crimes. The research method used is a normative legal research method, the approach method used is a qualitative approach that is descriptive and analytical, the type and source of data used is secondary data. Victims of physical violence often face challenges in obtaining adequate legal protection. This shows the importance of deepening the perspective of victimology in an effort to provide effective protection for victims of physical violence. Victimology as a science that studies victims of crime provides deep insight into the conditions, rights, and needs of victims of physical violence. By understanding the perspective of victimology, the legal system can be developed to be more responsive to the protection of victims of physical violence. This study aims to explore the extent to which existing legal protections have been able to protect victims of physical violence and assess whether these protections are in line with the principles of victimology. Through an in-depth analysis of existing aspects of legal protection, this study is expected to provide concrete recommendations for related parties to improve the effectiveness of protection for victims of physical violence. By paying attention to the perspective of victimology, it is hoped that legal protection efforts for victims of physical violence can be more focused on the needs of victims, provide easier access to justice, and prevent the recurrence of violence in the future. Alignment between the principles of victimology and the legal protection system is an important step in building a safer and more caring society for victims of physical violence.